2020
DOI: 10.1037/pas0000926
|View full text |Cite
|
Sign up to set email alerts
|

A psychometric evaluation of the Standardized Assessment of Severity of Personality Disorder (SASPD) in nonclinical and clinical German samples.

Abstract: Personality disorders (PD) are prevalent, underdiagnosed and affect clinical trajectories of psychiatric patients. The SASPD has been developed as a screening tool for PD severity according to the dimensional model of the initial ICD-11 proposal. We show that the SASPD total score might be useful as an indicator for a heterogeneous mixture of PD features, but less as a unidimensional measure of PD severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 48 publications
1
22
0
1
Order By: Relevance
“…Results suggest that the SIFS total score can be used with confidence as a screening tool for provisional assessment of PD severity; it showed a strong capacity, in five independent samples, to classify patients in categories that were meaningfully associated with a number of indices of externalizing and internalizing symptomatology relevant to PD. The present study should be seen as a positive step in the validation of time-efficient, accessible, and cost-effective clinical strategies to overcome the reluctance of some clinicians to diagnose PD, as it is often perceived as difficult, time-consuming, and off-putting [e.g., (29,77)]. Indeed, the empirically-based anchors presented in this study are straightforward in their interpretation, which is likely to make them appealing for screening purposes to many clinicians irrespective of their PD assessment expertise.…”
Section: Discussionmentioning
confidence: 99%
“…Results suggest that the SIFS total score can be used with confidence as a screening tool for provisional assessment of PD severity; it showed a strong capacity, in five independent samples, to classify patients in categories that were meaningfully associated with a number of indices of externalizing and internalizing symptomatology relevant to PD. The present study should be seen as a positive step in the validation of time-efficient, accessible, and cost-effective clinical strategies to overcome the reluctance of some clinicians to diagnose PD, as it is often perceived as difficult, time-consuming, and off-putting [e.g., (29,77)]. Indeed, the empirically-based anchors presented in this study are straightforward in their interpretation, which is likely to make them appealing for screening purposes to many clinicians irrespective of their PD assessment expertise.…”
Section: Discussionmentioning
confidence: 99%
“…Next, individuals who provide informed consent to take part in the study will undergo screening phone calls with licensed mindfulness-based meditation instructors. In these individual calls, participants will undergo mental health screening using the Standardized Assessment of Severity of Personality Disorder-Abbreviated Scale [ 192 ] and the Composite International Diagnostic-Screener [ 193 ]. These screening calls would further allow us to exclude individuals who are evaluated as meeting criteria for clinical diagnoses or psychological instability as identified by the meditation instructors, using the screening instruments.…”
Section: Methodsmentioning
confidence: 99%
“…A recent factor analytic study suggests that personality functioning, personality structure, and personality organization share a strong common factor [193]. Accordingly, several studies found high convergence between personality functioning and personality organization [35, 40, 41•, 48, 58, 194-196], personality functioning and personality structure [22, 40, 47•, 197], and personality structure and personality organization [40,78,89,140,[198][199][200]. It is noteworthy that studies successfully used recorded interviews for personality organization [48,59] and personality structure [47•] to assess personality functioning, suggesting that these concepts have sufficient informational overlap to extrapolate from one to the other (cf.…”
Section: Personality Functioning Personality Structure and Personality Organizationmentioning
confidence: 99%